Environmental aspects and sustainable management of green mussel culture in the north eastern part of the Bay of Bengal, Bangladesh and the Santubong river, Sarawak, Malaysia - Mohammed Ashraful, Azam Khan (Universiti Malaysia Sarawak (UNIMAS), 2012)
Biological study found that green mussels feed on zooplankton, phytoplankton, algae, detritus and partial digested food ranging from 47.5-6l.2%, 20.8-27.8%, 7.6-9.7%, 4.1-8.7% and 2.6-14.5% for males and 47.8-58.3%, 20.8-24.8%, 7.2-9.1 %, 5.2-8.4% and 5.8-1l.7% for females in the Bay of Bengal and 5l.2-55.6%, 2l.7-23.4%, 8.1-8.7%, 7.2-7.7% and 6.8-9.7% for males and 51.4-56.2%, 20.9-23.8%, 7.1-8.1%, 7.1-7.7% and 7.6-12.6% for females respectively in the Santubong River. The green mussel exhibits two spawning periods where temperature regulates the onset of reproductive events. Spat settlement densities are greater in the Bay of Bengal than the Santubong river waters. In rope culture mussel attains a marketable size of 50-60 mm in 6 months with an annual production of 47 kg m-I in the Bay of Bengal. The asymptotic length (Loo), growth co-efficient (K) and growth performance index (1)) were calculated as 11.55-13.65 cm., 0.97-l.80 year-I and 2.17-2.53 respectively in the Bay of Bengal and 9.45 cm., 1.10 yea{1 and 1.99 respectively in the Santubong River. The recruitment pattern was found continuous, displaying a double major peak event per year. The exponent 'b' value estimated was below 3 (b< 3) indicating that the growth pattern showed negative allometric growth.